Report on professional attachment with Learning Vision International Pte Ltd. - Goh, Catherine Lay Koon. (2009)
This PA report provides the reader with a good understanding of the background of the PA company to which I was attached. A thorough description fo two stimulating projects that I was responsible for can be found in Chapter Three of the report. During the 8 weeks, I wrote a business plan for a Book Club for LVI and carried out a test marketing. i also assist in the setting up a new child care centre at Nanyang Polytechnic. On the whole, it had been a very enriching and rewarding experience which I believed had better prepared me for working life.